IMPACT OF PATIENT COUNSELLING ON KNOWLEDGE, ATTITUDE, PRACTICES OF PATIENTS WITH TYPE 2 DM AT A TERTIARY CARE TEACHING HOSPITAL - George, Ajin K; Vg, Jewel; Manohar, Meenu; Kumar, Sarath P; J, Muneerudeen (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ObjectivesÂ To evaluate the impact of counselling in terms of KAP outcomes. MethodologyÂ A randomized prospective controlled study was conducted for a period of 6 months in the General Medicine OPD of SSIMS & RC. Patients enrolled were randomized into test and control groups. Suitably designed and validated KAP Questionnaire was applied at baseline and final follow up for both groups. Â ResultsÂ At the end of the study, knowledge and attitude levels were markedly improved in test group patients. The FBS of the patients in the test group were found to be significant (p<0.00) when compared from baseline to second assessement whereas in control group no significant changes were observed (*p> 0.05). ConclusionÂ The study concluded that the improved knowledge and attitude clearly indicates the benefits of pharmacist provided counselling, although they did not translate into improved practice outcomes. The study observed that, hospital pharmacists can play a key role in management of DM and patient care. Â Â